2012
DOI: 10.1111/j.1447-0594.2011.00813.x
|View full text |Cite
|
Sign up to set email alerts
|

Dietary pattern and mortality in Japanese elderly patients with type 2 diabetes mellitus: Does a vegetable‐ and fish‐rich diet improve mortality? An explanatory study

Abstract: Aim:To assess the effect of dietary patterns on all deaths and diabetes-related deaths in the Japanese Elderly Diabetes Intervention Trial (J-EDIT). Methods:We investigated relationships between that of overall mortality and dietary pattern, and diabetes-related deaths and dietary pattern as observed among 912 registered cases of the J-EDIT study, which is a prospective follow-up study of elderly Japanese type 2 diabetic patients.Results: Factor analysis with the factor number 3 led to deriving three dietary p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 24 publications
3
15
0
Order By: Relevance
“…The fact that groups with high intake of vegetables showed a dietary pattern similar to the “ prudent” dietary pattern suggests that “prudent” dietary patterns leads to improved HbA1c levels, even in elderly patients with type 2 diabetes mellitus. These results are in good agreement with results of Iimuro et al 29 . in this supplement.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The fact that groups with high intake of vegetables showed a dietary pattern similar to the “ prudent” dietary pattern suggests that “prudent” dietary patterns leads to improved HbA1c levels, even in elderly patients with type 2 diabetes mellitus. These results are in good agreement with results of Iimuro et al 29 . in this supplement.…”
Section: Discussionsupporting
confidence: 93%
“…27,28 The fact that groups with high intake of vegetables showed a dietary pattern similar to the " prudent" dietary pattern suggests that "prudent" dietary patterns leads to improved HbA1c levels, even in elderly patients with type 2 diabetes mellitus. These results are in good agreement with results of Iimuro et al 29 in this supplement. They showed a lower mortality rate in elderly type 2 diabetic patients with a dietary pattern of high intakes of vegetable and fish using elderly type 2 diabetic patients registered to J-EDIT.…”
Section: Effects Of Vegetable Intake On Hba1csupporting
confidence: 93%
“…The results of cohort studies showed that a sufficient intake of vegetables and fruit reduced the frequency of developing diabetes [16,17], and a diet high in dietary fiber containing vegetables might improve glycemic control [18,19]. Several studies conducted with elderly Japanese participants with T2DM demonstrated that diets rich in vegetables were correlated with improved HbA1c, serum triglyceride levels [20], and life prognosis [21]. Therefore, it is important to educate Japanese T2DM patients about the health advantages of consuming vegetables.…”
Section: Discussionmentioning
confidence: 99%
“…The factor rotation selected for this research was the same as those reported in previous studies on dietary pattern analysis that used factor analysis or principal component analysis: the orthogonal varimax 34,5,6,37,38,39,40 , the oblique promax 11,12,13,14,15 and direct oblimin 16,17 . In brief, the varimax is a type of orthogonal rotation that attempts to maximize the variance of squared loadings on a factor, i.e., to reduce the cross-loadings of the variables, leading to uncorrelated simple factor structures 41 .…”
Section: Food Groups Food Itemsmentioning
confidence: 99%
“…Orthogonal rotation leads to uncorrelated factors that are considered simpler and easier to interpret 8,10 , whereas nonorthogonal (oblique) rotation, such as promax and oblimin, allow producing correlated factors which are considered harder to interpret and, for this reason, have been used less in studies involving dietary pattern analysis 11,12,13,14,15,16,17 .…”
Section: Introductionmentioning
confidence: 99%